Shakespeare's First Folio and the fetish of the book. (July 2017) - Cummings, Brian
Prospero's renunciation of his book in The Tempest acknowledges its power as a kind of 'fetish'. This essay traces the idea of the book as 'commodity fetish' and as material text. The argument examines how post-Marxist thought, in a new reading of Louis Althusser, might be used to challenge the Shakespeare of late capitalism. It suggests how a complex reading of the fetish in historiography, combining a history of the material book in Shakespeare, with a theoretical reading of William Pietz, Stephen Greenblatt and Peter Stallybrass, sheds light on the First Folio, one of the most famous – and fetishized – books in history.